Setting the standard: The acceptability of kitchen ventilation for the English housing stock. (December 2019) - O'Leary, Catherine; Jones, Benjamin; Dimitroulopoulou, Sani; Hall, Ian P.
Abstract: Exposure to particulate matter with diameter ≤2.5 μm (PM2.5 ) is associated with an elevated risk of adverse health effects and cooking is a primary source of PM2.5 in non-smoking households. Therefore, it is important to investigate PM2.5 concentrations that might be found in domestic kitchens, and the appropriate ventilation mechanisms to reduce them. Uncertainty in daily mean PM2.5 concentrations in English kitchens is predicted using a statistical model and stochastic simulation. A worst-case heating season scenario is considered where 3 meals are cooked per day and fresh air is provided by infiltration and fans. The model predicts that >98% of English houses are too airtight to dilute PM2.5 emissions solely by infiltration so that daily mean concentrations in kitchens are below the WHO guideline of 25 μg/m 3 . Therefore, controlled ventilation is required in all kitchens. Ventilation strategies prescribed by English Building Regulations and ASHRAE 62.2 are found to be adequate for <12% and 75% of houses, respectively, when applied during cooking. Continuing to ventilate for a further 10 minutes has a significant effect when using an intermittent strategy, increasing the centiles of compliant houses to 46% and >98%, respectively. A cooker hood is the most effective ventilation strategy when used during cooking plus 10 minutes. Standards should be amended to incorporate required combinations of airflow rates and capture efficiencies. A hood with a capture efficiency of 50% requires airflow rates of 52 l/s and 90 l/s for PM2.5 concentrations to remain below WHO guidelines in 75% and 98% of houses, respectively. Highlights: Houses are too airtight to dilute PM2.5 emissions from cooking by infiltration. Controlled ventilation is required in all domestic kitchens. Ventilate during cooking plus 10 minutes has a significant effect. A cooker hood is the most effective method of pollutant control. Existing regulations of domestic kitchen ventilation require revision.